SIMULATION OF OBJECT MOTION WITH FRICTION ON A QUARTER CIRCLE USING VBA MACRO FOR EXCEL - Hadijah Binti Marfin, Sitti
The motion of an object on a curved path, especially in vertical circular motion with friction changes in magnitude and direction of speed continuously, this causes the acceleration vector of the object also changes. This study aims to make a simulation in order to understand changes in the velocity and the acceleration vector of the object using the VBA macro for excel. The method used is a numerical approach solution that is compared with the results of the Video Tracker experimentally. System in the form of objects are launched (without initial velocity) with friction in the form of a quarter circle, circle with a radius of 0.6 m using a height variation h of 0.6 m, 0.5 m, 0.4 m and 0.3 m. Then analyze the position, velocity, and acceleration of objects that usually use the law of conservation of energy as a solution to solve it, but in this study using kinematics equations or equations of object motion (Newton's second law). The results of this study are graphs of the position, velocity, and acceleration of objects with the angle ?. The relative error of the comparison of the final velocity of the simulation results and the experimental with variations of each height h is 7.019%, 6.468%, 5.278%, and 5.242%.